Crosstalk between STAT5 activation and PI3K/AKT functions in normal and transformed mammary epithelial cells. (15th August 2017) - Rädler, Patrick D.; Wehde, Barbara L.; Wagner, Kay-Uwe
Abstract: Janus kinases (JAKs) and signal transducers and activators of transcription (STATs) have been shown to function downstream of several peptide hormones and cytokines that are required for postnatal development and secretory function of the mammary gland. As part of an extended network, these signal transducers can engage in crosstalk with other pathways to facilitate synergistic, and sometimes antagonistic, actions of different growth factors. Specifically, signaling through the JAK2/STAT5 cascade has been demonstrated to be indispensable for the specification, proliferation, differentiation, and survival of secretory mammary epithelial cells. Following a concise description of major cellular programs in mammary gland development and the role of growth factors that rely on JAK/STAT signaling to orchestrate these programs, this review highlights the significance of active STAT5 and its crosstalk with the PI3 kinase and AKT1 for mediating the proliferation of alveolar progenitors and survival of their functionally differentiated descendants in the mammary gland. Based on its ability to provide self-sufficiency in growth signals that are also capable of overriding intrinsic cell death programs, persistently active STAT5 can serve as a potent oncoprotein that contributes to the genesis of breast cancer. Recent experimental evidence demonstrated that, similar to normal developmental programs, oncogenic functions of STAT5 rely on molecular crosstalk with PI3K/AKT signaling for the initiation, and in some instances the progression, of breast cancer. The multitude by which STATs can interact with individual mediators of the PI3K/AKT signaling cascade may provide novel avenues for targeting signaling nodes within molecular networks that are crucial for the survival of cancer cells.